Village Owned Enterprise Survival Strategy by Raising BrandAwareness of Advertising Through Marketing on Social Media - Kesa, Deni Danial (Jurnal Vokasi Indonesia, 2020)
The village as the center of economic development is always interesting to study, because the village structure in Indonesia generally supports the movement of the urban economy. The aim of this study was to analyze the role of marketing and self-image in one of the village organs, namely village-owned enterprises (BUMDes). One way of survival is how BUMdes can increase the brand awareness of the businesses and businesses they run. Quantitative research supporting by descriptive analysis is the method used. As one of the public services whose obligation is to obtain additional revenue through the business sector, BUMDes conducts marketing communications to consumers and expands marketing networks by improving self-image through two strategies. Direct strategies or below the line, use indirect prepositions. Respondents' results show that there are steps that need to be taken. In order to improve self-image, including through strategy, advertising and brand awareness, which are implemented for direct strategie. Indirect strategies can be implemented with activities or event activities as a spearhead. A good self-image will help the BUMDes business cycle to become stronger and support village programs as the center of the nation's economic progress.